Recommendations based on International Guidelines for Safe Dental Practice During Covid-19 - Singh, Ashutosh Kumar; Humagain, Manoj; Khanal, Nikita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
The shutdown of dental practices after the announcement of COVID-19 has been implemented worldwide. Aerosol generating procedures and face to face contact with the patients put dental professionals at highest risk of disease transmission. There is a looming risk of increasing severity of dental conditions and burden on treatment providers if required dental treatments are kept on hold for an indefinite time. There is a need for definite guidelines to safely resume dental practice in Nepal, based on international experiences during COVID-19 pandemic and international dental societies recommendations. We have compiled multiple recommendations and guidelines from reputed international organizations and collected evidence from dental professional’s work from China and Italy during COVID-19 crisis and attempted to put forward some recommendations and guidelines that can be followed for a safe dental practice in Nepal.